DETERMINAN KEJADIAN DIARE PADA BALITA - Hafsah, Hafsah; Yulidar, Elfina; Ngambut, Karolus; Gani, Kameriah (Ensiklopedia of Journal, 2024)
Abstract: Based on data obtained from the Sangir Health Center in 2022, there were 137 cases of diarrhea in toddlers, while in Nagari Lubuak Gadang there were 31 cases of diarrhea in the same age group. The purpose of the study was to determine the determinants of the incidence of diarrhea in toddlers. The research design used in this study was cross sectional. The research was conducted in July 2023 in the working area of Sangir Health Center Nagari Lubuk Gadang. The population is all families who have toddlers aged 12-59 months, in the Sangir Health Center working area in Lubuk Gadang nagari which amounts to 727 toddlers. The sample amounted to 31 toddlers. The sampling technique used simple random sampling. The research instrument used a research questionnaire. Data analysis was done univariate and bivariate. The results showed there was a relationship between latrine quality (p value: 0.001) and hand washing with soap behavior (p value: 0.021) on the incidence of diarrhea. It is recommended for health workers in the health promotion section of the Puskesmas to work together with other agencies such as the sub-district to conduct socialization in each village by providing health education on the importance of hand washing with soap.Keywords: Toddlers, Diarrhea, Latrine Quality.